"All‐on‐4" and "All‐on‐6" treatment concept applied using computer‐guided surgery in a patient: Case report with a 2‐year follow‐up. Issue 3 (14th March 2023) - Albaqawi, Ahmed Heji
Abstract: This case aimed to assess the clinical and radiographic outcomes of the All‐on‐4 and the All‐on‐6 concept using three‐dimensional computer‐assisted treatment planning, and computer‐guided surgery. Two years after the treatment, the "All‐on‐4" and "All‐on‐6" concepts provided effective treatment for immediate restoration and showed predictable outcomes in a completely edentulous patient.